Da lago a terra bonificata (1722-1962): l’uso dei GIS per la ricostruzione dell’area palustre dell’Estanque di Bellcaire d’Empordà (Catalogna) - Massimiliano Grava (Bollettino della Società Geografica Italiana)
The paper deals with the reconstruction of the history of the Estanque of Bellcaire d’Empordà, by the integration of traditional techniques of research with modern GIS information approaches. This area, administratively part of the comarca of the Baix Empordà, is located about seven kilometres from the Costa Brava, in the northernmost area of Catalonia. Traditional geo-historical research approach – based on the collection of the sources, analysis of the documents and the elaboration of a text – has been combined with technological approach of informatics sciences. As consequence of the introduction of GIS in geohistorical research, different sources and data (produced both by historians and by public institutions) have been compared; digitisation and GIS analysis of the sources allow to bring new light on the history of the areas, increasing our knowledge both under the quantitative and the qualitative perspectives.